Seismic fragility analysis of typical pre-1990 bridges due to near- and far-field ground motions - Mosleh, A. (2016)
Bridge damages during the past earthquakes caused several physical and economic impacts to transportation systems. Many of the existing bridges in earthquake prone areas are pre-1990 bridges and were designed with out of date regulation codes. The occurrences of strong motions in different parts of the world show every year the vulnerability of these structures. Nonlinear dynamic time history analyses were conducted to assess the seismic vulnerability of typical pre-1990 bridges. A family of existing concrete bridge representative of the most common bridges in the highway system in Iran is studied. The seismic demand consists in a set of far-field and near-field strong motions to evaluate the likelihood of exceeding the seismic capacity of the mentioned bridges. The peak ground accelerations (PGAs) were scaled and applied incrementally to the 3D models to evaluate the seismic performance of the bridges. The superstructure was assumed to remain elastic and the nonlinear behavior in piers was modeled by assigning plastic hinges in columns. In this study the displacement ductility and the PGA are selected as a seismic performance indicator and intensity measure, respectively. The results show that pre-1990 bridges subjected to near-fault ground motions reach minor and moderate damage states. (c) 2016, The Author(s).